Digital older people: use of information and communications technologies (ICT) associated with mood in older adults in the Metropolitan Area of ​​Guadalajara, Jalisco, Mexico - Mendoza Ruvalcaba, Neyda Ma. (2023)
ICTs have the potential to make resources available to the community, that help to improve people's quality of life and well-being. The objective of this study is to analyze the relationship between the use of information and communication technologies (ICTs), and depressive symptomatology in community-dwelling older adults in the Metropolitan Area of ​​Guadalajara, Mexico. A cross-sectional study was carried out, n=456 older adults participated, with prior informed consent, were evaluated by trained gerontologists who assessed the use of ICTs and mood through the presence of depressive symptoms. The results revealed that 53.9% of the participants used a cell phone, while 44.3% did not use any device, and 17.5% had depressive symptoms. The use of ICT was found to be related to depressive symptoms, specifically the lower use of ICT was associated with a greater presence of anhedonia, depressive mood, cognitive depressive symptoms, and feelings of worthlessness, and vice versa. Digital inclusion helps older adults to access the full exercise of their right to achieve healthy ageing.